VERBAL AND NON-VERBAL EXPRESSIONS IN TRADITION OF MOMBOLASUAKO (ELOPING) OF TOLAKI AT SOUTHEAST SULAWESI (ETHNOLINGUISTIC’S STUDY). - Pehala, Ilfan Askul; Fernandez, Inyo Yos; Abdullah, Wakit (PRASASTI: Journal of Linguistics, 2018)
This research aims to classify, describe and explain verbal and non-verbal expressions in eloping tradition (mombolasuako) of Tolaki based on the procession of eloping tradition (mombolasuako) of Tolaki comprehensively. Theories used to solve the problem of this are ethnolinguistics and ethnoscience. Methodologically, the ethnographic method was used in this. The data includes primary and secondary data that were collected by participant observation and deeply interview. All collected data were analyzed by using Spradely ethnoscience’s analysis and linguistics’ analysis. The outcomes of this research are verbal expressions in mombolasuako include verbal utterances, recitation and remark. For non-verbal expressions, they are (1) the tradition objects must be served by bride groom consists of process (2) gestures of tradition casts in the implementation of the traditions process and (3) tradition casts. In the implementation of the mombolasuako’s process verbal and non-verbal expressions verbal utterances, gestures and tradition casts that are adapted to tradition.  Key words: ethnolinguistics, mombolasuako, non-verbal expressions, Tolaki, verbal expressions